Morphological variation of the widely distributed genus Stenocorse Marsh, 1968 (Hymenoptera: Braconidae: Doryctinae) - González-Joya, Ancizar; Amarillo-Suárez, Ángela R.; Zaldivar-Riveron, Alejandro; Sarmiento, Carlos E. (Zootaxa, 2020)
Stenocorse is a monotypic genus with wide distribution and a large range of beetle hosts. We analyzed the morphological variation of 346 specimens from the USA south to Brasil. We studied 15 morphometric and 30 discrete characters using principal component (PCA) and discriminant function analyses (DFA) to assess character informativeness and the influence of geographic distribution and host source to detect differentiation. Mexican samples were studied according to location and biogeographic provinces. Specimens from Colombia were studied according to the plant where the host was recorded. Three measurements show group differentiation whereas four were redundant. Three groups of individuals were supported by continuous and discrete characters: one found in the USA, Mexico, Nicaragua and Costa Rica, a second from Mexico, and a third from Colombia and Brazil. These groups showed poor agreement with the differentiation of its common beetle host populations. This could be a consequence of the large number of sympatric host species feeding on a large number of plant species. This research shed light on other sources of evidence for building a sound taxonomy for Stenocorse.